Casino clubs, NSW profits, tax, sport and politics - Walker, Betty Con (Sydney University Press, 2009)
Casino Clubs NSW describes how big clubs have attained and retained a dominant position in the gaming industry. While recognising the positive role of small mutual clubs, it questions the continuing government support to big clubs through tax and regulatory concessions and it refutes claims that the bulk of gaming profits is spent on community contributions and sport sponsorship.